Thermal conductivity of argon–SiO₂ cryocrystal nanocomposite - Nikonkov, R.V.; Stachowiak, P.; Jeżowski, A.; Krivchikov, A.I. (Физика низких температур, 2016)
The effective thermal conductivity of samples of cryocrystal nanocomposite obtained from argon and SiO2
nanopowder was determined in the temperature interval 2–35 K using the steady-state method. The thermal conductivity
of crystalline argon with nanoparticles of amorphous silica oxide embedded in its structure shows a weak dependence
on particle linear dimension in the interval 5–42 nm. The temperature dependence of the thermal conductivity
of the nanocomposites can be well approximated by taking into account only the two mechanisms of heat
carrier scattering: phonon-phonon interaction in U-processes and scattering of phonons by dislocations.